Unpacking the role of universities in the emergence, development and impact of social innovations – A systematic review of the literature - Bayuo, Blaise Booponoyeng; Chaminade, Cristina; Göransson, Bo (Technological Forecasting and Social Change, 2020)
Widening income and knowledge inequalities have led to growing expectations for universities to integrate social innovation in their core missions as a response to societal problems. This systematic review of literature provides an overview of the state-of-the-art of knowledge on the role of the university in enabling social innovation through its missions of teaching, research and third mission. It also identifies knowledge gaps in the field. A bibliometric approach wasused to identify and analyze books, journal articles and reports examining factors driving social innovation activities at universities, organizational and insitutional change to accommodate such activities as well as their impact. The review reveals that the literature on university engagement in socially-oriented activities as part of the third mission of the university is conceptually well developed and a growing field of inquiry. It also points to gaps in the knowledge base; relatively few studies address issues related to institutional change and incentive structures that influences the ability of universities to engage in social innovation. Likewise, impact studies on social innovation activities at universities are scarce. Further research that builds an impact measurement framework would support the process of integrating social innovation activities in the three missions of the university.
Keywords: Innovation sociale; Mesure d'impact; Recherche; Réservé UdeM; Rôle des universités; Université